Smart Film From Chitosan–Anthocyanin Extracted From Allium cepa L. (Red Onion Skin) For Detecting Freshness of Chicken Meat - Kharizma Firdausi Nuzula; Cahyaning Rini Utami (University of Sultan Ageng Tirtayasa, 2025)
This study aimed to develop and evaluate a chitosan-based smart film incorporating anthocyanins extracted from red onion peel (Allium cepa L.) using a green extraction method for visual detection of chicken meat freshness. Anthocyanins were extracted via maceration using Deep Eutectic Solvent (DES) and 96% ethanol. DES extraction, recognized as an environmentally friendly alternative to conventional solvents, yielded approximately 35% higher anthocyanin content than ethanol. The smart films were prepared from chitosan, corn starch, and polyvinyl alcohol (PVA) at three PVA-to-anthocyanin ratios (1:1, 1:2, and 1:3) and tested on chicken meat stored at room temperature (5 days) and under refrigeration (10 days). Physical (thickness, tensile strength), chemical (moisture content, pH), and sensory (color, aroma, texture) analyses were conducted. Higher PVA concentrations improved film thickness and tensile strength, while chilled storage significantly reduced spoilage rates, indicated by lower pH and moisture values. Notably, the film exhibited a clear color transition from purple to greenish-yellow in response to pH changes associated with meat degradation, confirming its effectiveness as a pH-sensitive freshness indicator. The 1:3 PVA–anthocyanin formulation demonstrated optimal stability, responsiveness, and visual clarity. In conclusion, the developed chitosan-based smart film offers a sustainable, non-toxic, and efficient approach for monitoring chicken meat freshness, underscoring its potential as an eco-friendly intelligent packaging solution for ensuring food safety and quality.